SECURING THE RESTRICTED AREA AT INLET 491-AC1 FROM THE DANGER OF HOT MATERIAL DURING KILN UPSET BY INSTALLATION OF HEAT DETECTION EQUIPMENT AND MATERIAL SPILLAGE LEVEL - Rizkhi Nugroho; Hadi Kusnanto (Rekayasa Sistem Energi dan Manufaktur (ReSEM), 2024)
On February 18, 2023, an incident occurred at Tuban Plant factory. Namely a work accident that happened to a senior employee from the Fire & Rescue division. This incident occurred in a restricted area where evacuation access was limited and there was no telephone signal because it was located underground. Therefore, the author decided to make and install a safety device in the form of a temperature or heat detector and material level to provide warnings in the form of danger lights and sounds from horns in the area. After the tool is installed, temperature monitoring can be done on the local panel and also from the Technical Information System (TIS). After installation, from HIRAC calculations this tool succeeded in reducing the risk score by 95%, from initially 360 (high) to 18 (low). Apart from that, this tool can also save IDR 39,974,495 per hour from the initial handling time before the tool was 66.3 hours.